Composite material as well as preparation method and application thereof

By forming MOFs composite materials on the surface of graphene oxide and using coordination bond connections, the problem of insufficient CO2 adsorption performance and stability of MOFs materials is solved, and efficient CO2 capture and cost reduction are achieved. It is suitable for a variety of MOFs and substrates The combination of materials has enhanced the market application prospects.

CN119215858AActive Publication Date: 2024-12-31PETROCHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310774440.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The existing MOFs materials have shortcomings in CO2 adsorption performance and stability, especially the problems of low water stability and insufficient adsorption capacity. The large amount of base material added leads to high preparation costs and are limited to certain MOFs. Combination with substrate materials has limited applicability.

Method used

Graphene oxide is used as a support to form composite materials with metal organic compounds (such as UiO-66-OH, Cu-BTC, etc.), and use coordination bonds to prepare composite materials with high water stability, and heat reflux method Simplify the preparation process, control the addition amount of graphene oxide between 0.074% and 0.26%, and improve the adsorption performance of CO2.

Benefits of technology

It realizes efficient CO2 capture, improves the adsorption capacity and stability of MOFs, reduces the preparation cost, and is suitable for the combination of a variety of MOFs and substrate materials, improving the market competitiveness and application prospects of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215858A_ABST
    Figure CN119215858A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material as well as a preparation method and application thereof. The composite material is composed of a porous carbon material as a carrier and a metal organic compound as a precursor, wherein an oxygen group of the porous carbon material is connected with a metal center of the metal organic compound through a coordinate bond. The composite material is prepared by adopting a heating reflux method, the graphene oxide is used as a functional carrier, the high-water-stability graphene oxide loaded MOFs composite material is prepared, and after a very small amount of GO is added, the composite material shows that compared with MOFs, the composite material has relatively small aggregate particles, and the size of the composite material is relatively small. Due to coordination between oxygen groups in a graphene oxide sheet layer and metal centers in MOFs, aggregation of MOFs microcrystals is prevented, the dispersity of the MOFs microcrystals is improved, more adsorption active sites can be provided, the adsorption performance is improved, and the MOFs can be used for efficient capture of CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite material and a preparation method and application thereof. Background Art

[0002] As a typical greenhouse gas, carbon dioxide is mainly emitted through various social activities, such as the combustion of fossil fuels and various chemical processes. About 44% of the world's carbon dioxide comes from coal, oil, compressed natural gas (CNG) and fuel combustion. With the rapid development of industrialization, in order to meet the growing needs of mankind, energy consumption has increased rapidly. At present, about 85% of energy comes from the combustion of fossil fuels, which ultimately leads to a large amount of CO 2 To combat global climate change, CO 2 Capture and further utilize. In recent years, carbon capture technology has developed to a certain extent, among which the adsorption method has attracted widespread attention due to its simplicity, effectiveness and low cost. For adsorption materials, the adsorption characteristics are mainly affected by their specific surface area and pore volume. Among porous materials, inorganic-organic materials have received much attention in recent years.

[0003] MOFs (metal organic compounds) is a zeolite-like structure made of organic ligands and metal-containing clusters or metal nodes that are spontaneously assembled and connected to each other through covalent bonds or non-covalent bonds. This type of adsorbent has many advantages, such as a stable three-dimensional structure, a high specific surface area, a controllable pore structure, and an adjustable pore surface. The shape and size of MOFs materials can be regulated by selecting different metal ions and organic ligands to improve the adsorption or separation of gases. At present, MOFs materials are used in combination with different substrate materials to adjust the porosity of the composite material and promote its adsorption of gases. Common substrate materials are alumina, silica, carbon nanotubes, amorphous carbon, and graphene oxide (GO). Summary of the invention

[0004] In order to enrich the capture of CO 2 The invention provides a composite material for gas adsorption with strong stability and good adsorption performance.

[0005] As one aspect of the present invention, it relates to a composite material, which is composed of a porous carbon material as a carrier and a metal organic compound as a precursor; the oxygen group of the porous carbon material is connected to the metal center of the metal organic compound through a coordination bond.

[0006] In a specific embodiment, the porous carbon material is selected from graphene oxide material with a thickness of 0.3 to 1.0 nm and a sheet diameter of 0.5 to 10 μm.

[0007] In a specific embodiment, the metal organic compound is selected from UiO-66-OH, Cu-BTC, UiO-66, UiO-66-NO 2 , UiO-66-NH 2 , UiO-66-CH 3 One of them.

[0008] As another aspect of the present invention, it relates to a method for preparing the above composite material, the method comprising the following steps:

[0009] S1. Preparation of graphene oxide

[0010] Graphite powder and sodium nitrate were added to concentrated sulfuric acid in sequence and stirred evenly to obtain system A. After lowering the temperature of system A, KMnO 4 , heating the system to obtain system B; placing system B in an ice water bath, adding deionized water, and then placing it at room temperature, adding hydrogen peroxide to continue the reaction, washing, and drying to obtain graphene oxide;

[0011] S2. Preparation of graphene oxide suspension

[0012] The graphene oxide in S1 is dispersed in deionized water by ultrasonic treatment to obtain a graphene oxide suspension;

[0013] S3. Preparation of precursor solution

[0014] Adding a metal salt and an organic ligand into an acidic solvent, and reacting under stirring conditions to obtain a precursor solution;

[0015] S4. Preparation of composite materials

[0016] The graphene oxide suspension prepared in S2 is added to the precursor solution prepared in S3, and the mixture is evenly mixed to obtain system C. System C is placed in an oil bath for reaction, washed, and dried to obtain a composite material.

[0017] In a specific embodiment, in S1, the temperature of the system A is reduced to 0-5°C.

[0018] In a specific embodiment, in S1, the temperature is raised to 20-30°C and the reaction is carried out for 10-14 hours to obtain system B.

[0019] In a specific embodiment, in S1, hydrogen peroxide is added and the reaction is continued for 0.5 to 1 hour.

[0020] In a specific embodiment, in S2, the amount of graphene oxide added is 0.074% to 0.26% of the total mass of the reactants (i.e., graphene oxide, metal salt and organic ligand). Specifically, the mass fraction of graphene oxide added is 0.074% to 0.26%.

[0021] In a specific embodiment, in S2, the ultrasonic treatment time is 6 to 8 hours.

[0022] In a specific embodiment, in S3, the acidic solvent is selected from one of acetic acid, formic acid or oxalic acid.

[0023] In a specific embodiment, in S3, the metal salt is zirconium oxychloride or copper nitrate trihydrate.

[0024] In a specific embodiment, in S3, the organic ligand is selected from one of 2,5-dihydroxyterephthalic acid, terephthalic acid, 2-nitroterephthalic acid, 2-methylterephthalic acid, 2-hydroxyterephthalic acid, trimesic acid or 2-aminoterephthalic acid.

[0025] In a specific embodiment, in S4, the system C is placed in an oil bath at 100-120° C. for reaction for 18-24 hours.

[0026] As another aspect of the present invention, it relates to the application of the composite material mentioned above, wherein the composite material is applied as an adsorbent in the field of adsorption.

[0027] As another aspect of the present invention, it relates to a CO 2 A capture method using the composite material described above.

[0028] The present invention uses graphene oxide as a functional carrier to prepare a graphene oxide-loaded MOFs composite material with high water stability. After adding a very small amount of GO, the composite material shows smaller aggregated particles than MOFs, which is attributed to the coordination between the oxygen groups in the graphene oxide sheets and the metal centers in the MOFs, thereby preventing the aggregation of MOFs crystallites and increasing their dispersibility, providing more adsorption active sites to increase the adsorption performance, and can be used as a CO 2 Efficient capture.

[0029] The preparation method of the composite material provided by the present invention utilizes a heating reflux method, which is simpler than the commonly used hydrothermal reaction kettle method, and the composite material of graphene oxide loaded with metal organic compounds can be used for CO 2 The efficient adsorption of single MOFs on CO 2 It not only solves the problem of low adsorption capacity, but also solves the problem of low water stability of MOFs materials.

[0030] The present invention is not limited to the composite of graphene oxide and UiO-66-OH, but is also applicable to the combination with other MOFs, such as Cu-BTC, MOFs-Mg(74), etc. The composite material has a good effect on CO 2 The adsorption performance can also be significantly improved.

[0031] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the SEM morphology of the GO / UiO-66-OH composite adsorbent obtained in Example 1;

[0033] Figure 2 is the X-ray diffraction pattern of GO / UiO-66-OH obtained in Example 2;

[0034] Figure 3 This is the TGA graph of GO / UiO-66-OH obtained in Example 3;

[0035] Figure 4 The materials prepared in Examples (1, 2, 3) and Comparative Examples (1, 2, 3, 4) have a significant effect on CO 2 Adsorption effect diagram. DETAILED DESCRIPTION

[0036] When the inventors were exploring MOFs-related composite materials, they found that some researchers had reported a GO / UiO-66 composite material for CO 2 The addition of GO causes UiO-66 to react with CO 2 The adsorption performance of CO 2 The adsorption effect was not as expected; Professor Guan Guofeng of Nanjing University of Technology prepared a composite material of UiO-66 and graphene, which has a good adsorption effect on CO 2 It has a high adsorption capacity of 3.37mmol / g, which is 48% higher than that of single UiO-66 material; Professor Zhong Qin of Nanjing University of Science and Technology used Cu-BTC and mesoporous silica composites as CO 2 The adsorbents were also studied and compared with Cu-BTC, their CO 2 The adsorption capacity increased by 16% (HS-1: 108 cm 3 / g, 25℃ and 1.0bar); Lu Anhui's research group at Dalian University of Technology reported a porous carbon-Cu-BTC composite material for CO 2 The adsorption capacity is (22.7cm 3 / g), which is lower than that of single porous carbon 2 The adsorption capacity has been significantly improved.

[0037] Patent CN 116212831 A discloses a UiO-66-(OH) 2Preparation method of GO and its application in CO 2 However, the inventor believes that although this method can improve the material's adsorption of CO 2 The adsorption capacity of CO 2 The adsorption capacity is still insufficient, and the amount of GO added is large, resulting in a high preparation cost; moreover, the invention is limited to the combination of one substrate material and one MOFs, and is not suitable for the combination of other MOFs and substrate materials, which has certain limitations.

[0038] In summary, the stability of the above materials and their effects on CO 2 The adsorption capacity of the substrate is still lower than the inventor's expectation, and the amount of substrate material added is also large. Based on this, the inventor made the present invention through further research and development.

[0039] The present invention is further described below in conjunction with specific embodiments, and the protection scope of the present invention is not limited by the following embodiments. The sources of materials mainly involved in the following embodiments are shown in Table 1 below, and other materials not shown are conventional commercial products.

[0040] Table 1: Material source description

[0041] Serial number name Specification factory 1 Zirconium oxychloride octahydrate 98% Shanghai MacLean Biochemical Technology Co., Ltd. 2 2,5-Dihydroxyterephthalic acid 98% Shanghai MacLean Biochemical Technology Co., Ltd. 3 Terephthalic acid 98% Shanghai MacLean Biochemical Technology Co., Ltd. 4 2-Nitroterephthalic acid 98% Shanghai MacLean Biochemical Technology Co., Ltd. 5 Copper nitrate trihydrate 99% Shanghai MacLean Biochemical Technology Co., Ltd. 6 Trimesic acid 98% Shanghai MacLean Biochemical Technology Co., Ltd. 7 2-Methylterephthalic acid 98% Shanghai MacLean Biochemical Technology Co., Ltd. 8 2-Hydroxyterephthalic acid 98% Shanghai MacLean Biochemical Technology Co., Ltd.

[0042] The inventors have obtained the following preferred embodiments through a large number of experimental investigations, and provide Embodiments 1 to 9.

[0043] Example 1

[0044] A method for preparing a GO / UiO-66-OH composite adsorbent comprises the following steps:

[0045] S1. Preparation of graphene oxide

[0046] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 0 °C, 3.0 g of KMnO 4 , react at 20°C for 12h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 1h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0047] S2. Preparation of graphene oxide suspension

[0048] 2 mg (mass fraction of 0.074%, 2 mg / (1.7 g+1.0 g+2 mg)) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 7 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0049] S3. Preparation of precursor solution

[0050] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid in a single-necked flask, add 30 mL acetic acid, and react for 0.5 h under stirring to obtain a UiO-66-OH precursor dispersion;

[0051] S4. Preparation of composite materials

[0052] The graphene oxide suspension prepared in S2 is added to the UiO-66-OH precursor dispersion prepared in S3, and the mixture is evenly mixed to obtain system C; the system C is placed in an oil bath at a temperature of 100° C. to react for 24 hours to obtain a crude product of a composite material;

[0053] The crude product of the composite material was washed alternately with water and methanol for 6 times, with an interval of 12 h each time, to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120°C at a heating rate of 5°C / min and dried for 12 h to obtain a composite material of graphene oxide loaded with UiO-66-OH.

[0054] The scanning electron microscopy image of the GO / UiO-66-OH composite material synthesized in this example is shown in Figure 1 GO / UiO-66-OH and pure UiO-66-OH exhibit similar three-dimensional morphologies. No graphene oxide structure is found in the GO / UiO-66-OH material, which may be due to the small mass fraction of GO in the composite material and the smaller particle size of UiO-66-OH in the composite material, which only accounts for 0.074% of the precursor, and the increased particle dispersion is conducive to the improvement of adsorption performance.

[0055] Example 2

[0056] A method for preparing a GO / UiO-66-OH composite adsorbent comprises the following steps:

[0057] S1. Preparation of graphene oxide

[0058] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 2 °C, 3.0 g of KMnO 4, react at 25°C for 12h to obtain system B, place system B in an ice water bath, add deionized water, and then place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.8h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0059] S2. Preparation of graphene oxide suspension

[0060] 4 mg (mass fraction 0.15%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 6.5 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0061] S3. Preparation of precursor solution

[0062] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid in a single-necked flask, add 30 mL acetic acid, and react for 0.5 h under stirring to obtain a UiO-66-OH precursor dispersion;

[0063] S4. Preparation of composite materials

[0064] The graphene oxide suspension prepared in S2 is added to the UiO-66-OH precursor dispersion prepared in S3, and the mixture is evenly mixed to obtain system C; the system C is placed in an oil bath at a temperature of 100° C. to react for 24 hours to obtain a crude product of a composite material;

[0065] The crude product of the composite material was washed alternately with water and methanol for 6 times, with an interval of 12 h each time, to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120°C at a heating rate of 5°C / min and dried for 12 h to obtain a composite material of graphene oxide loaded with UiO-66-OH.

[0066] The XRD pattern of the composite material of this embodiment is as follows: Figure 2 shown.

[0067] The diffraction peaks of GO / UiO-66-OH are consistent with those of pure UiO-66-OH reported in the literature, indicating that the two materials were successfully prepared. The introduction of GO did not change the crystal structure.

[0068] Example 3

[0069] A method for preparing a GO / UiO-66-OH composite adsorbent comprises the following steps:

[0070] S1. Preparation of graphene oxide

[0071] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 5 °C, 3.0 g of KMnO 4 , react at 20°C for 12h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.5h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry in an oven at 60°C to obtain graphene oxide nanosheets;

[0072] S2. Preparation of graphene oxide suspension

[0073] 5 mg (mass fraction 0.18%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 6 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0074] S3. Preparation of precursor solution

[0075] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid in a single-necked flask, add 30 mL acetic acid, and react for 0.5 h under stirring to obtain a UiO-66-OH precursor dispersion;

[0076] S4. Preparation of composite materials

[0077] The graphene oxide suspension prepared in S2 is added to the UiO-66-OH precursor dispersion prepared in S3, and the mixture is evenly mixed to obtain system C; the system C is placed in an oil bath at a temperature of 100° C. to react for 24 hours to obtain a crude product of a composite material;

[0078] The crude product of the composite material was washed alternately with water and methanol for 6 times, with an interval of 12 h each time, to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120°C at a heating rate of 5°C / min and dried for 12 h to obtain a composite material of graphene oxide loaded with UiO-66-OH.

[0079] The TGA curve of GO / UiO-66-OH synthesized in this example is as follows Figure 3 The main temperature turning points of the composite material are consistent with each other. Two obvious weight loss steps are observed, which are similar to those of pure UiO-66-OH. The first step of weight loss below 280 °C is caused by the desorption of physically adsorbed water and small organic molecules. The second step of weight loss in the range of 280–500 °C may originate from the framework decomposition of the adsorbed material.

[0080] Example 4

[0081] A method for preparing a GO / UiO-66-OH composite adsorbent comprises the following steps:

[0082] S1. Preparation of graphene oxide

[0083] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 3 °C, 3.0 g of KMnO 4 , react at 30°C for 12h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.5h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0084] S2. Preparation of graphene oxide suspension

[0085] 7 mg (mass fraction 0.26%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 7.5 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0086] S3. Preparation of precursor solution

[0087] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid in a single-necked flask, add 30 mL acetic acid, and react for 0.5 h under stirring to obtain a UiO-66-OH precursor dispersion;

[0088] S4. Preparation of composite materials

[0089] The graphene oxide suspension prepared in S2 is added to the UiO-66-OH precursor dispersion prepared in S3, and the mixture is evenly mixed to obtain system C; the system C is placed in an oil bath at a temperature of 100° C. to react for 24 hours to obtain a crude product of a composite material;

[0090] The crude product of the composite material was washed alternately with water and methanol for 6 times, with an interval of 12 h each time, to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120°C at a heating rate of 5°C / min and dried for 12 h to obtain a composite material of graphene oxide loaded with UiO-66-OH.

[0091] Example 5

[0092] A method for preparing a GO / Cu-BTC composite adsorbent comprises the following steps:

[0093] S1. Preparation of graphene oxide

[0094] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 2 °C, 3.0 g of KMnO 4 , react at 25°C for 14h to obtain system B, place system B in an ice water bath, add deionized water, and then place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.8h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0095] S2. Preparation of graphene oxide suspension

[0096] 5 mg (mass fraction 0.26%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 8 h and then dispersed in 12 mL of deionized water to obtain a graphene oxide suspension;

[0097] S3. Preparation of precursor solution

[0098] Accurately weigh 0.875 g of copper nitrate trihydrate and dissolve it in the graphene oxide suspension prepared in S2; then accurately weigh 0.42 g of trimesic acid and dissolve it in 12 mL of anhydrous ethanol, and mix it with the above solution to obtain a mixed solution of the precursor;

[0099] S4. Preparation of composite materials

[0100] The precursor mixed solution prepared by S3 was transferred to a 200 mL polyethylene reactor, and the reactor was transferred to a drying oven for reaction at 120 ° C for 12 h. The reactor was cooled to room temperature, centrifuged and washed twice with 30 mL ethanol (speed of 8000 rpm), and finally the temperature was increased to 120 ° C at a heating rate of 5 ° C / min and dried for 10 h to obtain light blue powder crystals GO / Cu-BTC.

[0101] Example 6

[0102] A method for preparing a GO / UiO-66 composite adsorbent comprises the following steps:

[0103] S1. Preparation of graphene oxide

[0104] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 3 °C, 3.0 g of KMnO 4, react at 30°C for 12h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.5h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0105] S2. Preparation of graphene oxide suspension

[0106] 7 mg (mass fraction 0.20%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 7.5 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0107] S3. Preparation of precursor solution

[0108] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g terephthalic acid in a single-necked flask, add 30 mL formic acid, and react for 1 h under stirring to obtain a UiO-66 precursor dispersion; S4. Preparation of composite materials

[0109] The graphene oxide suspension prepared in S2 is added to the UiO-66 precursor dispersion prepared in S3, and the mixture is evenly mixed to obtain system C; the system C is placed in an oil bath at a temperature of 100° C. to react for 24 hours to obtain a crude product of a composite material;

[0110] The crude product of the composite material was washed alternately with water and methanol for 6 times, with an interval of 12 hours each time, to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120°C at a heating rate of 5°C / min and dried for 12 hours to obtain a composite material of graphene oxide loaded with UiO-66.

[0111] Example 7

[0112] A GO / UiO-66-NO 2 The preparation method of the composite adsorbent comprises the following steps: S1. Preparation of graphene oxide

[0113] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 3 °C, 3.0 g of KMnO 4 , react at 30°C for 10h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.5h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0114] S2. Preparation of graphene oxide suspension

[0115] 7 mg (mass fraction 0.26%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 7.5 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0116] S3. Preparation of precursor solution

[0117] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2-nitroterephthalic acid in a single-necked flask, add 30 mL oxalic acid, and react for 1 h under stirring to obtain UiO-66-NO 2 Precursor dispersion;

[0118] S4. Preparation of composite materials

[0119] The graphene oxide suspension prepared in S2 was added to the UiO-66-NO prepared in S3. 2 The precursor dispersion was mixed evenly to obtain system C; the system C was placed in an oil bath at a temperature of 100° C. to react for 24 hours to obtain a crude product of a composite material;

[0120] The crude composite material was washed alternately with water and methanol for 6 times, each time with an interval of 12 h to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120 °C at a heating rate of 5 °C / min and dried for 12 h to obtain graphene oxide-loaded UiO-66-NO 2 of composite materials.

[0121] Example 8

[0122] A GO / UiO-66-NH 2 The preparation method of the composite adsorbent comprises the following steps: S1. Preparation of graphene oxide

[0123] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 3 °C, 3.0 g of KMnO 4 , react at 30°C for 12h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.5h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0124] S2. Preparation of graphene oxide suspension

[0125] 7 mg (mass fraction 0.26%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 7.5 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0126] S3. Preparation of precursor solution

[0127] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2-aminoterephthalic acid in a single-necked flask, add 30 mL acetic acid, and react for 1 h under stirring to obtain UiO-66-NH 2 Precursor dispersion;

[0128] S4. Preparation of composite materials

[0129] The graphene oxide suspension prepared in S2 was added to the UiO-66-NH 2 The precursor dispersion was mixed evenly to obtain system C; the system C was placed in an oil bath at a temperature of 120° C. to react for 18 hours to obtain a crude product of the composite material;

[0130] The crude composite material was washed alternately with water and methanol for 6 times, each time with an interval of 12 h to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120 °C at a heating rate of 5 °C / min and dried for 12 h to obtain graphene oxide-loaded UiO-66-NH 2 of composite materials.

[0131] Example 9

[0132] A GO / UiO-66-CH 3 The preparation method of the composite adsorbent comprises the following steps: S1. Preparation of graphene oxide

[0133] 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 ml of concentrated sulfuric acid and stirred evenly to obtain system A. After the temperature of system A dropped to 3 °C, 3.0 g of KMnO 4 , react at 30°C for 12h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15ml of 30% hydrogen peroxide and continue to react for 0.5h, wash the reaction product with 5% hydrochloric acid solution and deionized water to remove excess acid and by-products, and dry it in an oven at 60°C to obtain graphene oxide nanosheets;

[0134] S2. Preparation of graphene oxide suspension

[0135] 7 mg (mass fraction 0.26%) of graphene oxide nanosheets prepared in S1 were ultrasonically treated for 7.5 h and then dispersed in 20 mL of deionized water to obtain a graphene oxide suspension;

[0136] S3. Preparation of precursor solution

[0137] Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2-methylterephthalic acid in a single-necked flask, add 30 mL acetic acid, and react for 1 h under stirring to obtain UiO-66-CH 3 Precursor dispersion;

[0138] S4. Preparation of composite materials

[0139] The graphene oxide suspension prepared in S2 was added to the UiO-66-CH 3 The precursor dispersion was mixed evenly to obtain system C; the system C was placed in an oil bath at a temperature of 100° C. to react for 24 hours to obtain a crude product of a composite material;

[0140] The crude composite material was washed alternately with water and methanol for 6 times, each time with an interval of 12 h to remove unreacted metal salts, organic ligands, and graphene oxide. Finally, the temperature was increased to 120 °C at a heating rate of 5 °C / min and dried for 12 h to obtain graphene oxide-loaded UiO-66-CH 3 of composite materials.

[0141] During the research stage, the inventor selected an experimental group with poor adsorption performance as a comparative example of the present invention, and provided comparative examples 1 to 5.

[0142] Comparative Example 1

[0143] The difference from Example 1 is that there is no carrier. Specifically, the preparation method of the UiO-66-OH adsorbent in this comparative example comprises the following steps:

[0144] (1) Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid into a single-necked flask, add 30 mL acetic acid and 20 mL water, and react for 0.5 h under stirring to obtain a UiO-66-OH precursor dispersion;

[0145] (2) The UiO-66-OH precursor solution in step (1) was placed in an oil bath at 100° C. for reaction for 24 h, washed alternately with water and methanol, and dried at 100° C. for 12 h to obtain a crystalline powder of UiO-66-OH.

[0146] Comparative Example 2

[0147] The difference from Example 2 is that the amount of graphene oxide added is different. Specifically, the preparation method of the UiO-66-OH / GO composite adsorbent in this comparative example comprises the following steps:

[0148] (1) 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 mL of concentrated sulfuric acid and stirred to obtain system A. System A was placed at a temperature of 0 to 5 °C and 3.0 g of KMnO was added. 4 , react at a temperature of 20 to 30° C. for 12 h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15 mL of 30% hydrogen peroxide and continue to react for 0.5 to 1 h, wash and dry to obtain graphene oxide;

[0149] (2) dispersing 10 mg (mass fraction 0.36%) of the graphene oxide prepared in step (1) into 20 mL of secondary water by ultrasonic treatment to obtain a graphene oxide suspension;

[0150] (3) Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid into a single-necked flask, add 30 mL formic acid, and react under stirring for 1 h to obtain a UiO-66-OH precursor dispersion;

[0151] (4) adding the graphene oxide suspension obtained in step (2) to the UiO-66-OH precursor solution obtained in step (3) and mixing them uniformly to obtain system C;

[0152] (5) placing system C of step (4) in an oil bath at 100° C. for reaction for 24 h, washing with water and methanol alternately, and drying at 100° C. for 12 h to obtain a composite material of graphene oxide loaded with UiO-66-OH.

[0153] Comparative Example 3

[0154] The difference from Example 3 is that the amount of graphene oxide added is different. Specifically, the preparation method of the UiO-66-OH / GO composite adsorbent in this comparative example comprises the following steps:

[0155] (1) 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 mL of concentrated sulfuric acid and stirred to obtain system A. System A was placed at a temperature of 0 to 5 °C and 3.0 g of KMnO was added. 4 , react at a temperature of 20 to 30° C. for 14 h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15 mL of 30% hydrogen peroxide and continue to react for 0.5 to 1 h, wash and dry to obtain graphene oxide;

[0156] (2) dispersing 20 mg (mass fraction of 0.74%) of the graphene oxide prepared in step (1) into 20 mL of secondary water by ultrasonic treatment to obtain a graphene oxide suspension;

[0157] (3) Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid into a single-necked flask, add 30 mL acetic acid, and react under stirring for 1 h to obtain a UiO-66-OH precursor dispersion;

[0158] (4) adding the graphene oxide suspension obtained in step (2) to the UiO-66-OH precursor solution obtained in step (3) and mixing them uniformly to obtain system C;

[0159] (5) The system C of step (4) was placed in an oil bath at a temperature of 100° C. for reaction for 20 h, washed alternately with water and methanol, and dried at 100° C. for 12 h to obtain a composite material of graphene oxide loaded with UiO-66-OH.

[0160] Comparative Example 4

[0161] The difference from Example 4 is that the carrier selection is different. Specifically, the preparation method of the UiO-66-OH / GO composite adsorbent of this comparative example includes the following steps:

[0162] (1) Weigh urea and distilled water in a mass ratio of 3:5 to prepare a mixed solution. Pour the mixed solution into a ceramic crucible, seal it and place it in a muffle furnace, heat it to 400°C at a heating rate of 10°C / min and keep it for 1 hour, then heat it to 550°C and keep it for 3 hours, and then cool it to room temperature. Dissolve the obtained light yellow loose block in distilled water and ultrasonicate it for 1 hour, then put it in a drying oven to dry, take it out and grind it to obtain gC 3 N 4 powder;

[0163] (2) Step (1) gC 3 N 4 7 mg was dispersed into 20 mL of secondary water by ultrasonic treatment to obtain gC 3 N 4 Suspension;

[0164] (3) Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2-hydroxyterephthalic acid into a single-necked flask, add 30 mL acetic acid, and react under stirring for 1 h to obtain a UiO-66-OH precursor dispersion;

[0165] (4) Step (2) 3 N 4 The suspension is added to the UiO-66-OH precursor solution in step (3) and mixed evenly to obtain system C;

[0166] (5) Place the system C in step (4) in an oil bath at 100°C for 24 hours, wash with water and methanol alternately, and dry at 100°C for 12 hours to obtain gC 3 N 4Composite materials loaded with UiO-66-OH.

[0167] Comparative Example 5

[0168] The difference from Example 4 is that the amount of graphene oxide added is different. Specifically, the preparation method of the UiO-66-OH / GO composite adsorbent in this comparative example comprises the following steps:

[0169] (1) 1.0 g of graphite powder and 0.5 g of sodium nitrate were added to 24 mL of concentrated sulfuric acid and stirred to obtain system A. System A was placed at a temperature of 0 to 5 °C and 3.0 g of KMnO was added. 4 , react at a temperature of 20 to 30° C. for 12 h to obtain system B, place system B in an ice water bath, add deionized water, place at room temperature, add 15 mL of 30% hydrogen peroxide and continue to react for 0.5 to 1 h, wash and dry to obtain graphene oxide;

[0170] (2) dispersing 1 mg (mass fraction of 0.04%) of the graphene oxide prepared in step (1) into 20 mL of secondary water by ultrasonic treatment to obtain a graphene oxide suspension;

[0171] (3) Accurately weigh 1.7 g zirconium oxychloride and 1.0 g 2,5-dihydroxyterephthalic acid into a single-necked flask, add 30 mL formic acid, and react under stirring for 1 h to obtain a UiO-66-OH precursor dispersion;

[0172] (4) adding the graphene oxide suspension obtained in step (2) to the UiO-66-OH precursor solution obtained in step (3) and mixing them uniformly to obtain system C;

[0173] (5) placing system C of step (4) in an oil bath at 100° C. for reaction for 24 h, washing with water and methanol alternately, and drying at 100° C. for 12 h to obtain a composite material of graphene oxide loaded with UiO-66-OH.

[0174] Performance Testing

[0175] The following performance tests were performed on the above Examples 1 to 9 and Comparative Examples 1 to 5, and the test results are recorded in Table 2 below.

[0176] Adsorption performance test: TStarII-3000 physical adsorption instrument produced by Micromeritics, USA, was used to measure the CO 2 Adsorption isotherms in the pressure range from 0.01 to 760 mmHg were obtained according to the literature “Two microporous CoII-MOFs with dual active sites for highly selective adsorption of CO 2 / CH4 and CO 2 / N 2 ” (Dalton Trans., 2019, 48, 13541-13545) was used to conduct the experiment. The specific steps are as follows: accurately weigh a certain mass of adsorption material into a sample tube, vacuum pre-treat it at 120°C for 4 to 8 hours, and then measure the adsorption isotherm at 25°C. The measurement data results are shown in Table 2, and the graphical results are shown in Appendix Figure 4 .

[0177] Table 2 Adsorption performance test results

[0178]

[0179] Combining the above experiments, the data results in Table 2 and the attached Figure 4 , we can get:

[0180] The solid adsorbents prepared in each embodiment and comparative example were used to prepare CO 2 The adsorption capacity of CO is shown in Table 2. 2 The adsorption capacity is 4.12 mmol / g, which is due to the large specific surface area, pore volume and metal sites of MOFs. In order to improve the pore utilization of MOFs, graphene oxide is introduced to adjust the properties of the pores. Compared with comparative example 1, graphene oxide is added to examples 1 to 4. The composite adsorbent prepared under this condition has a higher adsorption capacity for CO 2 The adsorption capacity has been improved to a certain extent, mainly because the introduction of graphene not only increases the specific surface area, but also forms new pores.

[0181] In Comparative Example 1, graphene oxide was not added. In Comparative Examples 2 to 3, the mass fraction of graphene oxide was increased, which reduced the CO 2 The adsorption capacity of MOFs was reduced due to the excessive addition of graphene oxide, which blocked some pores of MOFs and caused a decrease in adsorption performance. 2 The adsorption amount of CO did not change or did not change significantly. Based on this, the inventors believe that the mass fraction of graphene oxide added is too small, which has a significant effect on CO 2 The adsorption of graphene oxide cannot improve or significantly improve the CO 2 absorption rate. In addition, the inventors also believe that the preparation cost of graphene oxide is high, which will increase the production cost during large-scale production, thereby reducing the economic benefits. Therefore, in the present invention, the mass fraction of graphene oxide added is reasonably controlled between 0.074% and 0.26%, that is, a very small amount (in milligrams) of graphene oxide can improve the CO 2 absorption rate of the composite material. 2 The adsorption performance not only reduces the production cost and improves the market competitiveness, but also has a better market application prospect.

[0182] Compared with Example 4, the carrier in Comparative Example 4 was replaced with gC 3 N 4 , gC 3 N 4 The introduction of 2 The adsorption capacity of gC 3 N 4 No specific coordination structure is formed between the MOFs and the nanostructured carbon nanotubes, only pore blockage occurs.

[0183] According to the above analysis results, graphene oxide was finally determined as the added carrier, and the added mass fraction was 0.26%. At the same time, other types of MOFs or UiO-66 with different functional groups and GO were investigated, and similar effects were obtained.

[0184] Combining the product examples of the present invention and the comparative examples, it can be seen that the present invention realizes the composite adsorbent for CO by in-situ generation of MOFs on the surface of graphene oxide. 2 The improvement of adsorption capacity gives it certain application prospects in carbon capture.

[0185] The above are only preferred feasible embodiments of the present invention, and the protection scope of the present invention is not limited thereto. Various modifications or applications made according to the above embodiments are within the protection scope of this technical solution.

[0186] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.

Claims

1. A composite material, characterized in that: The composite material is composed of a porous carbon material as a carrier and a metal organic compound as a precursor; the oxygen group of the porous carbon material is connected to the metal center of the metal organic compound through a coordination bond.

2. The composite material according to claim 1, characterized in that The porous carbon material is selected from graphene oxide material with a thickness of 0.3 to 1.0 nm and a sheet diameter of 0.5 to 10 μm.

3. The composite material according to claim 1, characterized in that The metal organic compound is selected from one of UiO-66-OH, Cu-BTC, UiO-66, UiO-66-NO2, UiO-66-NH2, and UiO-66-CH3.

4. A method for preparing the composite material according to any one of claims 1 to 3, characterized in that: The method comprises the following preparation steps: S1. Preparation of graphene oxide Graphite powder and sodium nitrate are added to concentrated sulfuric acid in sequence, and stirred evenly to obtain system A; after lowering the temperature of system A, KMnO4 is added, and the temperature is raised to react to obtain system B; system B is placed in an ice water bath, deionized water is added, and then placed at room temperature, hydrogen peroxide is added to continue the reaction, and then washed and dried to obtain graphene oxide; S2. Preparation of graphene oxide suspension The graphene oxide in S1 is dispersed in deionized water by ultrasonic treatment to obtain a graphene oxide suspension; S3. Preparation of precursor solution Adding a metal salt and an organic ligand into an acidic solvent, and reacting under stirring conditions to obtain a precursor solution; S4. Preparation of composite materials The graphene oxide suspension prepared in S2 is added to the precursor solution prepared in S3, and the mixture is evenly mixed to obtain system C. System C is placed in an oil bath for reaction, washed, and dried to obtain a composite material.

5. The method for preparing a composite material according to claim 4, characterized in that: In S1, the temperature of the system A is reduced to 0-5°C.

6. The method for preparing a composite material according to claim 4, characterized in that: In S1, the temperature is raised to 20-30°C and the reaction is carried out for 10-14 hours to obtain system B.

7. The method for preparing a composite material according to claim 4, characterized in that: In S1, hydrogen peroxide is added and the reaction is continued for 0.5 to 1 hour.

8. The method for preparing a composite material according to claim 4, characterized in that: In S2, the mass fraction of the added graphene oxide is 0.074% to 0.26%.

9. The method for preparing a composite material according to claim 4, characterized in that: In S2, the ultrasonic treatment time is 6 to 8 hours.

10. The method for preparing a composite material according to claim 4, characterized in that: In S3, the acidic solvent is selected from one of acetic acid, formic acid or oxalic acid.

11. The method for preparing a composite material according to claim 4, characterized in that: In S3, the metal salt is zirconium oxychloride or copper nitrate trihydrate.

12. The method for preparing a composite material according to claim 4, characterized in that: In S3, the organic ligand is selected from one of 2,5-dihydroxyterephthalic acid, terephthalic acid, 2-nitroterephthalic acid, 2-methylterephthalic acid, 2-hydroxyterephthalic acid, trimesic acid or 2-aminoterephthalic acid.

13. The method for preparing a composite material according to claim 4, characterized in that: In S4, the system C is placed in an oil bath at 100-120° C. for reaction for 18-24 hours.

14. Use of the composite material according to any one of claims 1 to 13, characterized in that: The composite material is used as an adsorbent in the adsorption field.

15. A method for capturing CO2, characterized in that: The method uses the composite material according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Graphene oxide and copper-containing coordination polymer composite material and microwave synthesis method thereof

    CN104645940A

  • Preparation method of MOFs / graphene adsorption material

    CN106064052A

  • Preparation method of graphene oxide loaded UIO-66 composite material and application thereof

    CN111013544A

  • Carboxyl modified graphene oxide-metal organic framework composite material and preparation method and application thereof

    CN111266091A

  • Preparation method and application of MOF-based composite material adsorbent for CO2 / N2 adsorption separation

    CN116212831A